Reframing Marketing Innovation in Economic Development: Evidence from Indonesia on Inclusion and Resilience - Egie Sofian Nuddin (proceedings.icesy, 2026)
This study examined the role of marketing innovation as a driver of inclusive and resilient economic development in Indonesia. The research addressed the problem of limited understanding regarding how marketing innovation contributes not only to firm-level performance but also to broader economic inclusion and resilience, particularly in developing country contexts. A qualitative research approach was employed using document analysis of policy documents, institutional reports, and academic publications related to marketing innovation, economic development, and resilience in Indonesia. The study applied thematic content analysis to identify key patterns and strategic orientations embedded within the documents. The findings revealed that marketing innovation functioned as a mechanism for expanding market access, reducing structural barriers for micro, small, and medium enterprises, and enhancing adaptive capacity in response to economic disruptions. Marketing innovation was found to support inclusive economic participation through digital marketing practices, innovative distribution channels, and customer-centered value creation strategies. Additionally, the results indicated that marketing innovation strengthened economic resilience by enabling flexibility, responsiveness, and sustainability within dynamic market environments. The study concluded that marketing innovation operated at organizational, market, and institutional levels and should be understood as a multidimensional development instrument rather than solely a business strategy. These findings highlighted the importance of aligning marketing innovation with institutional frameworks and development policies to support inclusive, resilient, and sustainable economic growth. The study contributed an interdisciplinary perspective by integrating marketing management, innovation studies, and development economics.